Carcinoma arising in ectopic hamartomatous thymoma. An ultrastructural study - Michal, M; Neubauer, L; Fakan, F (Pathology, research and practice, 1996)
We present the ultrastructural features of a case of adenocarcinoma arising in ectopic hamartomatous thymoma in a 31 year old man, in the supraclavicular location. The tumor had a cribriform adenomatous component with a granular cell quality and mimicked a metastatic carcinoma. Ultrastructurally, the spindle cell component revealed clusters of tonofilaments and the tumor cells were attached by well developed desmosomes. The cytoplasm of adenocarcinoma cells contained peculiar cup-shaped bodies derived from the endoplasmic reticulum wrapped around the mitochondria.
Keywords: Thoracic Diseases; Adenocarcinoma; thymom; Adult; dospělí; adenokarcinom; hamartom; sekundární malignity; Thymoma; Humans; Neoplasms, Second Primary; mužské pohlaví; Male; lidé; nemoci hrudníku; Thoracic Neoplasms; nádory hrudníku; Hamartoma